We are given with two functions: f(x) = x + 8 and g(x) = x2 - 6x - 7. In this problem, the value of f(g(2)) is asked. We first substitute g(x) to f(x) resulting to f(x2 - 6x - 7) = x2 - 6x - 7 + 8 = x2 - 6x + 1. If x is equal to 2, then <span>f(g(2)) = 2^</span>2 - 6*2 + 1 equal to -7.
Step-by-step explanation:
G = (z-s) ÷ r
G × r = (z- s)
Gr + s = z
Answer:
a. 126
b. 15120
Step-by-step explanation:
5 chose 9 = 9 * 8 * 7 * 6 * 5/1/2/3/4/5 = 126
if order matters...
9*8*7*6*5 = 15120
It is the same as 100 it is 15/100